Ageing in travel - Carvalho, Alessandra Silva (2013)
The significant increase in the elderly population in the world has fostered the interest of some fields of knowledge. Regarding the field of tourism is notorious discussion about aging, once the elderly represent potential travellers and the variety of opportunities seems almost limitless these days. Based on these findings, this article proposes to discuss the aspects that relate aging to tourism. Seeking to improve the quality of life of elderly patients, following the trip peculiarities and improving the time of travel for the elderly. This is a qualitative research that apply a semi-structured questioner to seven elderly people who travel regularly, there were extensive content analysis with the data collected. The results in this survey pointed that in the 21st century industry has begun reshaping itself to accommodate older travelers with special services and in order to make their stay more comfortable, that Indicated important developments on the relevant role of these trips for the sociability of such individuals.